Analysis of Gamification Utilization in the GO Expert App for English Learning as a Foreign Language - Nurul Husnul Awaliyah; Abdullah; Nur Aeni (Program Studi Magister Pendidikan Bahasa Inggris, Fakultas Bahasa dan Sastra- Universitas Negeri Makassar., 2026)
This study analyzes the use of gamification in the GO Expert App for learning English as a foreign language, focusing on students' perceptions and the factors that support and inhibit its use. A qualitative approach was employed, using thematic analysis according to Creswell & Creswell (2023). The participants in this study were five twelfth-grade students from Ganesha Operation, selected through purposive sampling. Data were collected through in-depth interviews, observations, and documentation, and then analyzed using the six steps of thematic analysis. The results of this study indicate that students hold a positive perception of gamification in the GO Expert App. Elements such as leaderboards, points, stars, and timed quizzes are considered capable of increasing motivation to learn, fostering a competitive spirit, and encouraging students to be more active in English learning activities. Additionally, students rated learning through this App more engaging and less monotonous than conventional methods at their school. Practice questions with immediate feedback help students understand English material independently and continuously. The study also identified supporting factors such as peer support, teacher guidance, attractive features, ease of use of the App, and immediate feedback, which contribute to behavioral, emotional, and cognitive engagement in learning. However, there are inhibiting factors, including technical issues, unclear features, cognitive load from long texts, and distractions from other applications on students' mobile devices. Overall, this study concludes that gamification in the GO Expert App plays an important role in enhancing students' motivation, engagement, and understanding in learning English as a foreign language. However, improvements in technical aspects and design are needed to optimize its use.